2011
DOI: 10.1007/s00464-011-1806-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of atypical extra-esophageal reflux symptoms following laparoscopic antireflux surgery

Abstract: In an unselected cohort of patients undergoing LARS, atypical GERD symptoms improved as significantly as typical symptoms. Symptom improvement was significantly lower in the presence of esophageal hypomotility and with higher symptomatic state. Therefore, patients with severe atypical symptoms or hypomotile esophagus may not achieve the same clinical satisfaction from LARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…Moreover, there was no difference in the rates of complete symptom control according to the presence of atypical symptoms. The results of this study also support the findings of Brown et al [14], who described a good response to laparoscopic Nissen fundoplication in GERD patients with atypical symptoms after judicious evaluation and proper patient choice.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, there was no difference in the rates of complete symptom control according to the presence of atypical symptoms. The results of this study also support the findings of Brown et al [14], who described a good response to laparoscopic Nissen fundoplication in GERD patients with atypical symptoms after judicious evaluation and proper patient choice.…”
Section: Discussionsupporting
confidence: 91%
“…8,[23][24][25] Chest pain symptom resolution in these studies ranged from 48% to 96% with fundoplication, regardless of the type of surgery. 7,[22][23][24] In one study, 87% of patients with NCCP treated with surgical fundoplication stated that they would consider the operation again if needed 22 (Table 2). Some studies have shown no difference in chest pain symptom scores after surgical fundoplication in patients with documented oesophageal dysmotility as the underlying cause of NCCP.…”
Section: Proton Pump Inhibitors (Ppis)mentioning
confidence: 77%
“…In one study, a significant improvement in atypical symptoms (including chest pain) was seen in patients with normal and spastic oesophageal motility patterns treated with surgical fundoplication (72.4% vs. 83.9%, respectively) compared to pre‐operative symptom scores ( P = 0.04). Those patients with hypocontractile oesophageal motor disorders had improved symptoms (21.7%), but at a lower rate of improvement compared to those with spastic or normal oesophageal motility patterns (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…The concept of tailoring the fundoplication (partial vs. complete) based upon manometric findings of ineffective esophageal motility is debated [37]. However, information on esophageal contractility is helpful to prognosticate the outcome, if not to influence the selection of a partial fundoplication [4,38,39].…”
Section: Antireflux Surgerymentioning
confidence: 99%